Marginal Community and Their White Kebaya: Penghayat Sapta Darma and the Purity Discourse in Jakarta - Siti Khoirnafiya (Universitas Andalas, 2020)
Penghayat is often marginalized with heretical and syncretic stigma. However, the negative stigma is not true for them. They believe their “religion” is pure and not a splinter from any religion. It represented by their Kebaya. The existing literature or previous studies on the Kebaya of Penghayat is limited. Therefore, this study specifically aimed to discuss their Kebaya, with case the Sapta Darma community in Jakarta. This research was conducted with a qualitative approach, through an interview, observation, and literature study techniques. Then in data analysis tend to use interpretive symbolic and discourse analysis of material. This study found that the material (Kebaya) is an important part in disclosing identity to